Moderation and Civilization (A Historical Analysis on the Moderate Policy of the Rustamid Dynasty) - Rofiq, Ahmad Choirul (ARISTO, 2018)
The Rustamid Dynasty (160-296 AH / 776-909 AD) was a remarkable Ibadite dynasty. Unfortunately, most of the historical works have paid little attention to the development of Islamic civilization during the Rustamid reign. This fact is very contrary to the study of Sunnite or Shi’ite dynasties. This paper shows that the Rustamids performed their moderate policy by giving great tolerance, freedom, and equality to all citizens who lived in their territory, especially in Tahert (part of Algeria) and Jabal Nafusah (part of Libya). Consequently, this moderate policy, which was encouraged by the moderate Ibadite doctrine, had influence on the establishment of Islamic civilization in the Maghrib. The Rustamids successively played a significant role in economic prosperity, intellectual development, and Islamization. Like the Rustamids, the plural society of Indonesia can obtain the achievements of civilization by maintaining their multicultural diversity. Hence, the Indonesian government, the Muslim organizations, and all of the Muslim people should promote tolerant Islamic teachings and support intellectual movement.